Forecasting Of Storage Duration Of Long-Term Storable Food Products - Sergey V. Shterman, Mikhail Yu. Sidorenko, Yuri I. Sidorenko, Valery V. Ugrozov, Nadezhda M. Podgornova,Sergey M. Petrov, Natalya I. Chebotareva (International Journal of Advanced Science and Technology, 2020)
The present research offers a method for predicting storage conditions at possible temperature fluctuations (elevated temperatures). The analysis with the help of the developed mathematical model reveals that temperature fluctuations during storage of food products have a minor effect on the permissible shelf life. Here, the critical factor is the average temperature during long-term storage of food products.